DiGRA Chapter Diversity - Wirman, Hanna (Transactions of the Digital Games Research Association, 2018)
This paper focuses on the perceived value and importance of the regional chapters of Digital Games Research Association (DiGRA). Drawing on a survey conducted among chapter representatives, the viewpoints of nine regional chapter representatives are discussed, particularly from the point of view of how they contribute to better diversity and inclusiveness in such a large international organization. It answers two questions: “What are the advantages of having regional chapters?” and “What exactly constitutes ‘regional’ in the context of DiGRA chapters?” In so doing, the paper establishes regional chapters as important junctures in catering for a wide audience beyond those able and interested in participating in annual DiGRA conferences or partaking in other international events.